Paul Maenz Jahresbericht 1976. - Paul Maenz, Köln (Köln : Paul Maenz, 1977)
Buren, Daniel ; Toroni, Niele ; Roehr, Peter ; Barry, Robert ; Sartor, Paolo Mussat ; Bertholin, Jean-Marie ; Paolini, Giulio ; Rutault, Claude ; etc.
Duits
boek